A Digital Twin and User-Preference Based Trust Computation (DTUPTC) Model for Federated Cloud Computing Environment - SARAF, V.; PACHGHARE, V. (Advances in Electrical and Computer Engineering)
Cloud computing has become an integral part for many organizations as well as cloud users. There are several cloud service providers hosting numerous cloud services. The challenge for the cloud users is to find the suitable cloud service among all cloud service providers which is most trusted and meets user expectations. The authentic and accurate trust values for such cloud services can help organizations and cloud users to choose appropriate cloud services. In this paper, we propose a Digital Twin and User-Preference Based Trust Computing (DTUPTC) model which is based on evidence-based strategy of trust computation. The novelty of our DTUPTC model is that we get the user inputs on their preferred quality of service (QoS) attributes which will be used for trust score computation and also provide their desired values for those QoS attributes. The weights assigned to each QoS attributes while computing trust score are calculated and assigned automatically without any manual intervention. The comparison results of our DTUPTC model with other models proves that the trust scores computed by DTUPTC model are more accurate than the other models.